Ethical Practice Disclosure of Malaysian Public Listed Companies - Firdhauz Zainul Abidin, Ahmad; Aishah Hashim, Hafiza; Salleh, Zalailah; Devi, Susela (KnE Social Sciences, 2019)
The Malaysian business world has seen a series of scandals amongst government-related companies in recent years, including 1Malaysia Development Berhad (1MDB), Lembaga Tabung Haji (LTH), Felda Global Ventures (FGV) and Khazanah Nasional Berhad (KHAZANAH). Despite having strong corporate governance policies, in addition to the Malaysia Code of Corporate Governance (MCCG), unethical practices and a lack of transparency remain a problem. This paper examines the level of disclosure of ethical practices by Malaysian public listed companies. Ethical practice disclosure is measured using the modified Ethical Commitment Index (ECI) with six themes derived from the literature: corporate ethical values; action to promote ethics; whistle-blowing policy; code of ethics; sustainability practices; and ethics committee. Conducting analysis of the annual reports of 1,115 companies across five years (2012-2016), this study found there is a need to improve several aspects of ethical practice disclosure. Although the findings suggest that companies supported the MCCG, with most of the companies complying with the recommendations of MCCG 2012 to uphold a high standard of ethical practice, supplementary practices (such as disciplinary action, programmes to support a code of ethics, whistle-blowers’ protection, and establishing an ethics committee) are still weak. This study suggests that regulator action is required to improve the level of ethical practice disclosure by Malaysian public listed companies.